Fungistatic Activity of Crude Protein Extracted from Bacillus subtilis HJX1 - Zhao Gengfeng Qiu Yimin Zhang Yunxia Xiong Guoru (Plant Diseases and Pests(植物病虫害研究：英文版), 2015)
Bacillus subtilis HJX1, a biocontrol strain of Fusarium oxysporum f. sp. cubense, could inhibit growth of several plant pathogenic fungi in vitro. To un- derstand its mechanism of fungistasis, we extracted crude protein from fermentation broth of the strain HJX1 through ammonium sulfate precipitation, and prelimina- rily studied fungistatic activities at different conditions. The results showed that the crude protein was insensitive to protease K, trypsin or ultraviolet radiation. The fungistatic activity was unchanged when treated in water batch at 40 ℃, 60 ℃, 80 ℃ or 100 ℃ for 30 min, and the fungistatic activity maintained 60% when trea- ted at 121℃ for 30 min.